The Power of Choice: A Study Protocol on How Identity Leadership Fosters Commitment Toward the Organization - Mascarenhas, Mafalda F.; Dübbers, Felix; Hoszowska, Magdalena; Köseoğlu, Aylin; Karakasheva, Ralitsa; Topal, Ayse B.; Izydorczyk, David; Lemoine, Jérémy E. (Frontiers in Psychology, 2018)
Identity leadership (IL) describes that the effectiveness of a leader will depend upon his capacity to represent a given group, to make the group go forward, to create a group identity, and to make the group matter. An identity leader may increase commitment among his followers by increasing the perception of shared identity and giving more weight in the decision process to his followers. We aim to explore the mechanisms through which a leader who creates a shared group identity can increase organizational commitment. In the first study, we plan to conduct a cross-cultural correlational study where we aim to test if the relationship between IL and organizational commitment is mediated by team identification and mediated-moderated by participation in decision making (PDM) and collective efficacy. In the second study, we aim to explore the direction of the causality between IL and PDM. To test this hypothesis, we will conduct an experimental study in which (1) we will manipulate IL to test its influence on the perception of PDM and (2) we will manipulate PDM to test its influence on the perception of IL. Thus, we will be able to identify the role of IL and the perception of PDM on organizational commitment.